INVESTIGATION OF BLOOD MONONUCLEAR CELLS CYTOKINE-PRODUCTION FUNCTION FROM PATIENTS WITH MULTIPLE SCLEROSIS TREATED WITH THE ENDOGENOUS RETROVIRUS HERV-E λ 4-1 CONSERVATIVE REGION SYNTHETIC OLIGOPEPTIDE - I. A. Goldina (SPb RAACI, 2021)
Considering to the data of class I human endogenous retrovirus HERV-Е λ 4-1 subgroup association with multiple sclerosis, an autoimmune disease accompanied by neuroinflammation, changes in the neurotransmitters level, progressive neurological dysfunction, as well as the ability of this retrovirus to replicate and to produce proteins with potential immunomodulatory properties, the aim of this work was a comparative study of the blood immune cells cytokine synthesizing function in conventionally healthy individuals and multiple sclerosis patients under the synthetic 17 – amino acid oligopeptide homologous to the hydrophobic transmembrane protein р15Е HERV-Е λ 4-1 conserved region influence. The 40 patients, 17 male persons aged 38.0 (31.0-47.0) years old and 23 female persons aged 39.0 (31.0-50.0) years old with an established diagnosis of multiple sclerosis (G 35, ICD-10), corresponding to the McDonald 2005, modified in 2010 criteria with a continuously progressive disease course and the disease duration of 17.0 (14.0-18.0) years, and 30 conditionally healthy individuals, 12 male persons aged 32.0 (23.0-43.0) years old and 18 female persons aged 36.0 (29.0-46.0) years old were the objects of the study. An open-label, observational, single-center, cohort, controlled, randomized trial was conducted. It was found that the donor’s blood mononuclear cells IL-1β, IL-6, TNFα, IFNγ and IL-2 spontaneous production in culture was stimulated, but that of IL-4 and IL-10 did not change under the retroviral oligopeptide influence. At the same time, the spontaneous and mitogenstimulated production of all studied cytokines did not change under the control oligopeptide influence. The PHA-stimulated donor’s blood mononuclear cells cultivation in presence of the retroviral oligopeptide, as compared to the control one, was accompanied by an increase in the IL-1β, IL-6 and TNFα release into the culture supernatant. The multiple sclerosis patients were characterized by IL-1β, IL-6 and IFNγ higher content in the mitogen-unstimulated blood mononuclear cells culture supernatant, compared with conditionally healthy individuals, as well as by a higher production of IL-6 and IFNγ in response to PHA stimulation. The retroviral oligopeptide, in contrast to the control one, stimulated the IL-1β, IL-6, TNFα and IFNγ spontaneous production without altering that of IL-4 and IL-10 in multiple sclerosis patients. The obtained results indicate that the synthetic oligopeptide homologous to the conserved region of the hydrophobic transmembrane protein p15E HERV-Е λ 4-1 has the pro-inflammatory properties, which is probably the one of human endogenous retrovirus HERV-Е λ 4-1 pathological abilities realization mechanism in multiple sclerosis.